The underlying concept of Persian miniature paintings: Persian miniature paintings between 14th to 17th centuries / Mohammad Tirani - Tirani, Mohammad (Institute of Graduate Studies, UiTM, 2018)
Since Nineteen century until now many fine artists and art historians from western countries and also Muslim scholars tried to reveal the underlying techniques and content behind the Persian Miniature Paintings. Most of the early outcome of Western analysis and research works emphasized on decorative concept of miniature paintings until past decades that some Western and Persian-Muslim scholars like Henry Corbin, Oleg Grabar, Robert Hillenbrand, SH NASR, M. M. Ashrafi and many others started new argument about philosophicalmystical concept behind the miniature works. To unlock the mysteries of creating miniature works researchers referred to mystical philosophy of Iran in that period. After that the great Sufis’ names like as Shahab al-Din Suhrawardi, Jami, Molana, Maulana Rumi, Ibn ‘Arabi and many others entered the analytic language of Persian Miniature Arts. There are many publications and research works in the past decades that explained the relation between artists and Sufis but until now no one able to propose an aesthetical term and language for Persian miniature works. Beside historical, literal and formal analysis; researchers required to establish an acceptable and accurate terms which proved the connections between miniature works and mystical concepts…